The coffee agroecosystem: traditional polyculture versus commercial polyculture in Chocamán, Veracruz - Pérez-Vázquez, Arturo; Pérez-Sánchez, Olivia; Lango-Reynoso, Verónica; Escamilla-Prado, Esteban (Revista Mexicana de Ciencias Agrícolas, 2024)
Coffee cultivation has strong social and historical-cultural roots in the mountainous area of the state of Veracruz. Its ancestral cultivation was carried out in agroforestry systems, the original pattern of which has been modified. The association of coffee with cash crops is conceived as an option to address its low profitability. Therefore, the objective was to compare the level of sustainability of traditional polyculture coffee versus commercial polyculture coffee in three communities in Chocamán, Veracruz during 2021. A survey and a sampling were carried out to estimate plant and soil biodiversity; a physical-chemical analysis of the soil was also performed. Regarding the environmental aspect, organic matter had a higher percentage in commercial polyculture coffee. In the economic dimension, commercial polyculture coffee was 50% more profitable compared to traditional polyculture coffee. On the social side, there were differences in schooling, age of producers, off-farm activities, level of organization and type of agriculture. It was concluded that commercial polyculture coffee had better economic indicators, while traditional polyculture coffee achieved better environmental and social indicators.